Frequency of Malnutrition among children under 2 Years and Its Relationship with Inadequate Breast Feeding Practice - Ashraf, Samia; Iftikhar, Nosheen; Ahmed, Shabir; Ahmad, Waheed; Sultan, Allah Nawaz; Butt, Nayyab (Pakistan Journal of Medical & Health Sciences, 2022)
Background: In developing countries malnutrition is a serious child health issue. Almost 50%of 10.7 million deaths per year in developing countries are due to Malnutrition in children less than five years of age. It has been turn up that 20% of low weight children younger than five years belong to low and middle income countries with Pakistan contributing as the 3rd largest share of underweight children in world. Aim: To know the frequency of malnutrition in children younger than 2 years of age, presenting at a tertiary care hospital and to compare the frequency of inadequate breast feeding practices among well-nourished and malnourished children. Methods: A Cross Sectional Study was conducted from 10-10-2019 to 09-04-2020 in Paediatrics unit Sharif Medical City Hospital, Lahore. About 151 healthy children presenting for routine growth monitoring and immunization or with acute ailments of less than 3 days duration in previously healthy children presenting to the paediatric unit were included in this study. The written consent was taken from parents before enrolling in this study. Information regarding their demographic data and history of breast feeding was noted in the proforma. All the children with appropriate age underwent measurement of weight in minimum light clothes using standard protocols and were assessed for weight for age. Results: From 151 patients, age ranges was 3 months to 24 months with mean and standard deviation was 14.01±6.43 months. The weight of children was observed as 6.5 kg to 13.0kg with mean and standard deviation was 9.05±1.88.In Gender distribution Male patients were 55.6% and female 44.4%. Mothers having no formal education were 35.8% and mothers having formal education were 64.2%. There were 39.7% fathers having no formal education and 60.3% fathers having formal education. There were 19.9% patients in which malnutrition was present while 80.1% respondents in which malnutrition was not present. There were 23.8% mothers who were practicing inadequate breast feeding methods while 76.2% mothers who were practicing adequate breast feeding methods. The frequency of inadequate breast feeding practice among well-nourished was found as 7.28% and 16.56% among malnourished children. Conclusion: There were 19.9% respondents in which malnutrition was present. The frequency of inadequate breast feeding practice among well-nourished was found as 7.28% and 16.56% among malnourished children. Significant association was found between malnutrition and inadequate breast feeding. Effect modifiers like age and gender did not show significant influence except weight and parental education.